Potential public health impacts of gonorrhea vaccination programmes under declining incidences: A modeling study. - Lin Geng; Lilith K Whittles; Borame L Dickens; Martin T W Chio; Yihao Chen; Rayner Kay Jin Tan; Azra Ghani; Jue Tao Lim (PLoS Medicine)
Background Gonorrhea is the second most common sexually transmitted disease notified in Singapore in 2023. Evidence suggests that the 4CMenB vaccine designed to protect against Neisseria meningitidis infection may offer partial cross-protection against gonorrhea. This generated interest in using 4CMenB for the purpose of staving gonorrhea transmission. We explored the efficacy of potential gonorrhea vaccination strategies in the context of historically declining gonorrhea incidence. Methods and findings We employed an integrated transmission-dynamic model, calibrated using Bayesian methods to local surveillance data to understand the potential public health impact of 4CMenB in reducing gonorrhea acquisition and transmission in men who have sex with men (MSM) in Singapore. We explored the efficacy of implementing six vaccination programmes: (1) offering vaccination to all male adolescents in schools (vaccination before entry [VbE]), (2) offering vaccination to individuals attending sexual health clinics for testing (vaccination on attendance [VoA]), (3) offering vaccination to individuals attending sexual health clinics and who were diagnosed with gonorrhea (vaccination on diagnosis [VoD]), or (4) vaccination according to risk (VaR), by offering vaccination to patients who were diagnosed with gonorrhea plus individuals who tested negative, but report having more than five sexual partners per year. We further examined how altering (5) VoA and (6) VoD strategies changed if the strategies only targeted high risk groups (VoA(H),VoD(H)). We assessed efficacy by examining vaccination impact relative to no vaccination and when behavioral parameters were held constant. We further ascertained the effects of varying vaccine uptake (10%, 33%, 100%), vaccine efficacy (22%, 31%, 47%), and duration of protection (1.5, 4, 7.5 years) on the effectiveness of each vaccination strategy. For a hypothetical 10-year vaccination programme, VbE had 14.18% of MSM gonorrhea cases averted over the time the programme was implemented. VoA had the highest protective impact on the MSM population with 40.26% averted cases (95% credible interval (CrI): 18.32%-52.57%), but required more vaccine doses than any other strategy. VoD had a smaller impact (12.04% averted cases (95% CrI: 7.12%-15.00%)), but was three times more efficient than VoA in terms of averted cases per dose. VoA(H) and VoD(H) improved the efficiency of VoA and VoD strategies by increasing averted cases per dose to 0.22 and 0.24 respectively, but conferred similar protective effects as VoA (VoA(H): 40.10% averted cases (95% CrI: 18.14%-52.55%)) and VoD (VoD(H): 12.04% averted cases (95% CrI: 7.12%-15.00%)), respectively. VaR (40.10% averted cases (95% CrI: 18.14%-52.55%)) had almost the same impact as VoA, but was more efficient by requiring administration of fewer doses than VoA, with 0.21 (95% CrI: 0.12-0.27) averted cases per dose. Sensitivity analyses indicated that VaR had the greatest public health impact with the highest number of averted cases per dose for vaccines of any efficacy or duration of protection (or both), although VoD and VoD(H) saved more vaccine resource and had the highest number averted MSM cases per dose for highly protective vaccines of long protection. Conclusions Vaccination of MSM against gonorrhea, according to risk in sexual health clinics in Singapore, can be considered to reduce gonorrhea acquisition and transmission. Development of gonorrhea-specific vaccines which focuses on protective efficacy and the implementation of efficient vaccination programmes can maximize public health impact.